Boredom and its perceived impact in adolescents with exceptional mathematical talent: a sequential mixed-methods study in Paraguay - Vuyk, Alexandra; Montania, Maureen; Barrios, Liz (Frontiers in Sociology, 2024)
Boredom, a state where the task at hand presents difficulties in attentional resources and attributed meaning, can be detrimental to talent development by reducing cognitive engagement. This study employed a mixed sequential design to assess boredom in adolescents with exceptional mathematical talent in Paraguay participating in a talent development program. First, in the quantitative phase 54 students completed the Boredom Short Scale, School Attitudes Assessment Survey-Revised, and Psychological Well-Being Scale for Adolescents. Next, in the qualitative phase 50 students participated in focus groups to explore their personal experiences of boredom, along with their perception of possible valuation of goals and academic self-perception related with a lower tendency towards boredom only in the context of a talent development program, but not at school. Boredom seemed multifaceted, with dimensions such as the absence of meaning, superficial entertainment, and wasted time. Contributing factors included waiting for other people's slower pace, limited choices, lack of novelty, insufficient intellectual challenge, and the influence of teachers and social dynamics. Coping mechanisms included inner intellectual stimulation, seeking entertainment and escape, pursuing independent learning, extracurricular activities, like-minded peers, and extreme sensation-seeking. Fostering adequate challenge and support in advanced academic endeavors for the development of mathematical talent can prevent negative consequences associated with boredom in exceptionally talented populations.